Diversity and Allelopathic Potential of Weeds in Swampland - Sujinah, Sujinah; Margaret, Swisci; Agustiani, Nurwulan; Ningsih, Rina Dirgahayu; Rumanti, Indrastuti Apri (Department of Agrotechnology, Universitas Muhammadiyah Yogyakarta, 2023)
Weeds are plant disturbing organism that affect yields through competition and allelopathy. However, not much is known about weed diversity in swamps, so research is needed to identify their types and compounds as a weed control strategy. This study was conducted using a survey method from January to March 2020 at the Barito Kuala District, South Kalimantan. Thirty villages were randomly selected from each of the eight chosen subdistricts. Out of the twenty-six weed species identified, there were ten species of grasses, seven sedges, and nine broadleaves. The results showed that the weed species were dominated by Cyperus halpan, Eleocharis dulcis, and Cynodon dactylon (L.), with an SDR of 23.46, 16.73, and 10.03, respectively. The analysis of GC-MS showed that the weeds contained four similar compounds: neophyte diene, palmitic acid, linoleic acid, and stigmasterol. The largest compound content in C. halpan was diisocotyl phthalate (48.49%), while in E. dulcis and C. dactylon the largest were o-phthalic acid and mono-2-ethylhexyl-ester (69.36 and 40.23%). Moreover, weed allelochemicals are classified into fatty acids, steroids, esters, and other volatile compounds, where some have the potential for allelopathy that inhibits crop growth.